Reconstituição de um corpo de obra: arte, vida, museus e os diferentes modos de habitá-los - Cohen, Ana Paula Carvalho (2020)
The thesis presented departs from the archive developed by Suely Rolnik, Arquivo para uma obraacontecimento. Projeto de ativação da memória corporal de uma trajetória artística e seu contexto [Archive for a work-event. Project to activate the body memory of an artistic trajectory and its context] – which brings to the present the artistic practice of Lygia Clark, as well as the context in which it was developed. It seeks to outline contemporary artistic practices that can be thought of as obra-acontecimento [work-event]: practices that do not manifest themselves only through objects, but that are imbued by vital force, sensitive to the context in which they are performed, and connected to the present space and time in which they are presented. Considering that these practices guided my professional path as a curator in the last two decades, there is an emphasis on exhibition apparatus that bring these art practices to the public, whether for the first time or seeking to re-present them with their original force; the art exhibition conceived as a place of reception, which provides a continuous actualization of the art works in relation to the space and to the body of the audience. The reconstitution of a body of work, as proposed in this thesis, is achieved by non-linear, non-objective and non-chronological operations, and it seeks to bring to the present practices defined by the intensity of life proliferated in the bodies involved in each project. Such reconstitution is not based on a repetition of the original form of what was once an art work, an exhibition or even a fixed history defined by specific facts. New devices are needed to its actualizations, capable of activating a living force with similar intensity to the project that are being reconstituted, in order to reverberate in the bodies that come into contact with that device in the present. A clinical thought that understands the creative act, as well as its actualizations, as unblocking the passages of life, bringing health to the individual and collective bodies. In this sense, there is a proposition of what we could call a museu-acontecimento [museum-event], a museum whose emphasis would not be on collecting objects of value, but which could prioritize the breaths of life deposited in each artistic proposition: a clinical device in the continuous actualization of the creative act